Prenatal RSVpreF Vaccination Uptake Associated with Non-English Primary Language During Its First Season at a Federally Qualified Health Center - Corinne Thornton; Samina Bhumbra (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background RSV and bronchiolitis are major causes of hospitalizations and death among infants. The RSVpreF vaccine was approved and released in 2023 for pregnant women to prevent severe RSV in infants during their first RSV season. This is the first prenatal vaccine recommended since the COVID-19 vaccine was approved. However, other prenatal vaccination rates have remained low with a rise in overall vaccine hesitancy in recent years. Our cross-sectional study describes and compares the sociodemographic characteristics and health behaviors associated with first-season receipt of the RSVpreF vaccine among women receiving prenatal care at a federally qualified health center (FQHC). Methods Medical records of pregnant women with prenatal care visits at an Indianapolis, IN FQHC between 9/26/2023 and 3/31/2024 were reviewed and screened for RSVpreF vaccine eligibility. Vaccination status (RSVpreF, TDaP, influenza, and COVID-19), demographic information, obstetric history, adequacy of prenatal care, preferred language, and social determinants of health were collected. Corresponding infant charts were reviewed for nirsevimab and 2-month immunizations and breastfeeding status. Women who received the RSVpreF vaccine were compared to those who did not get the vaccine using statistical analyses. Results Of 344 women eligible for the RSVpreF vaccine, 78 (23%) received the vaccine and 266 (77%) did not. Nine (2.6%) infants received nirsevimab. More women who received the RSVpreF vaccine spoke a preferred language other than English (81%) compared to those who did not receive the vaccine (66%) (P=0.0138). More women received adequate prenatal care (53%) in the RSVpreF vaccinated group compared to the unvaccinated group (37%) (P=0.0128) and had 0.88 more prenatal care visits (P=0.0241). The RSVpreF vaccinated group also received the TDaP and influenza vaccines more often, but both groups were above national average vaccination rates. There were no significant differences in race/ethnicity, age, gravida/parity, health insurance, transportation barriers, food insecurity, and housing instability. There were no differences in infant immunization and breastfeeding. Conclusion The presence of a language barrier often limits navigation of the healthcare system due to logistical difficulties, including requiring interpreter services. Likewise, immigration status influences seeking medical care and health insurance coverage. However, our study shows the opposite effect that those who primarily spoke languages other than English were more likely to receive the new RSVpreF vaccine than those who spoke English. Whether cultural factors have a larger influence than expected on pregnant women receiving new vaccines compared to logistical constraints from other social determinants of health requires further investigation.